The Forensic Autopsy Record: A Type of Medical Record or Not? - ika meilia, putri dianita (Jurnal Forensik dan Medikolegal Indonesia, 2019)
Forensic pathology is a part of (forensic) medicine that has unique features compared to other medical specialties. One of them is that the results of forensic pathological examinations are not documented in medical records but in forensic autopsy records (FARs). Despite the existence of regulations regarding medical records and the performance of (forensic) autopsies, FARs themselves are rarely mentioned in detail. This paper aims at reviewing current issues regarding FARs and discussing whether FARs can be considered as a type of medical record or not. Our literature review yields that there exist guidelines regarding the management of FARs, e.g. in the USA and Europe. Indonesia, however, lacks similar guidelines. There are several ethical and medico-legal issues present regarding FARs, which should be addressed, as FARs cannot be considered as a type of MRs. PDFI can play an important role in developing guidelines regarding FARs, which should be adopted by Indonesian forensic medical centres to avoid ethical and medico-legal pitfalls.